2019
DOI: 10.3171/2018.3.jns173224
|View full text |Cite
|
Sign up to set email alerts
|

Interfacility neurosurgical transfers: an analysis of nontraumatic inpatient and emergency department transfers with implications for improvements in care

Abstract: OBJECTIVE Interfacility neurosurgical transfers to tertiary care centers are driven by a number of variables, including lack of on-site coverage, limited available technology, insurance factors, and patient preference. The authors sought to assess the timing and necessity of surgery and compared transfers to their institution from emergency departments (ED) and inpatient units at other hospitals. METHODS Adult neurosurgical patients who were transferred to a single tertiary care center were analyzed over 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…Avoidance of interfacility transfer is associated with potential cost savings [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [22] . Arnold et al retrospectively reviewed the records of TBI patients with GCS 13–15 transferred to a level 1 trauma center in their respective hospital system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoidance of interfacility transfer is associated with potential cost savings [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [22] . Arnold et al retrospectively reviewed the records of TBI patients with GCS 13–15 transferred to a level 1 trauma center in their respective hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a common reason for transfer to trauma centers for neurosurgical evaluation [1] , [2] , [3] , [4] , [5] , [6] . Results from a recent TRACK-TBI study revealed that less than 50% of patients with so-called “mild” TBI (i.e., Glasgow Coma Score (GCS), 13–15) reported full return to pre-injury levels of day-to-day function at one-year post-injury [7] , highlighting the need for further study of long-term functional limitations in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…This holds true emphatically for neurosurgical patients, for whom both avoidable IHT and inefficient transfer infrastructure leave room for quality improvement. In one series of neurosurgical patients, 57.4% of IHT led to no surgical intervention and in another one 34.5% IHTs were non-operative [1,2]. The direct transportation costs for avoidable transfers amounted to $1.46 million over two years in a study of neurosurgical IHT [2].…”
Section: Introductionmentioning
confidence: 99%
“…In one series of neurosurgical patients, 57.4% of IHT led to no surgical intervention and in another one 34.5% IHTs were non-operative [1,2]. The direct transportation costs for avoidable transfers amounted to $1.46 million over two years in a study of neurosurgical IHT [2].…”
Section: Introductionmentioning
confidence: 99%
“…6 Prior systematic studies have described general patterns of EMTALA enforcement, 6 resulting fines, [7][8][9][10] impact of the law on on-call coverage, 11 and patterns of EMTALA transfers for surgical subspecialty care. [12][13][14][15][16][17] Despite the fact that labor is the only medical condition named in the title of the law, EMTALA violations related to labor and other OB emergencies have not previously been systematically described in the peer-reviewed medical literature.…”
Section: Introductionmentioning
confidence: 99%